2012
DOI: 10.1177/001979391206500109
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Anti-Discrimination and Workers' Compensation Laws on the Provision of Workplace Accommodations following the Onset of a Disability

Abstract: The Americans with Disabilities Act of 1990 (ADA) was the first federal disability-based anti-discrimination law that applied to a broad range of workers. Whereas some studies have focused on its impact on workplace accommodation, this is the first to do so while accounting for previous state anti-discrimination and Workers' Compensation laws. Using data from the Health and Retirement Study, the authors find that prior to the implementation of the ADA, employers were more likely to accommodate workers if their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…This evidence is consistent with Burkhauser et al (2012), who used the Health and Retirement Study (hRs) and reported accommodations by respondents who had a wide range of disabilities. 1 Moreover, in a study of nearly 60,000 claims filed under the ADA, Feurerstein, Luff, Harrington, and Olsen (2007) found that only 2.9% of them were related to cancer.…”
supporting
confidence: 85%
“…This evidence is consistent with Burkhauser et al (2012), who used the Health and Retirement Study (hRs) and reported accommodations by respondents who had a wide range of disabilities. 1 Moreover, in a study of nearly 60,000 claims filed under the ADA, Feurerstein, Luff, Harrington, and Olsen (2007) found that only 2.9% of them were related to cancer.…”
supporting
confidence: 85%
“…Estimates of the percentage of employees with disabilities who receive accommodations vary considerably, from 12 percent to 65 percent (Burkhauser, Schmeiser, & Weathers, ; Hernandez et al, ; Zwerling et al, ). Surprisingly, there is little information on how many accommodation requests are made, the percentage that are accepted versus denied, and for those that are denied, why they are denied.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Disability had a special interest from regulators in the USA; the Americans with Disabilities Act of 1990 (ADA) was the foremost law aimed to dissolve any form of inequality and unfairness in hiring and compensating disable persons (Burkhauser, Schmeiser, & Weathers , 2012). Thanem (2008) indicated that this type of diversity requires more attention to go beyond what medical reports considered as disability.…”
Section: Human Resources Diversity and Diversity Dimensionsmentioning
confidence: 99%